Efficacy and Safety of Risperidone and Quetiapine in Adolescents With Bipolar II Disorder Comorbid With Conduct Disorder. Issue 5 (October 2015) - Masi, Gabriele; Milone, Annarita; Stawinoga, Agnieszka; Veltri, Stefania; Pisano, Simone
<x xml:space="preserve">Abstract</x> Abstract Although a frequent co-occurrence between bipolar disorder (BD) and conduct disorder (CD) in youth has been frequently reported, data about pharmacological management are scarce and focused on BD type I. Second generation antipsychotics are frequently used in clinical practice, but no comparative studies are available. The aim of this exploratory study was to compare efficacy and safety of risperidone and quetiapine in a sample of adolescents presenting a BD type II comorbid with CD. Twenty-two patients diagnosed with a structured interview according to Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, (male/female ratio, 12/10; mean (SD) age 15.0 (1.4) years) were randomized in 2 treatment groups (quetiapine [n = 12] vs risperidone [n = 10]), treated with flexible doses, and followed up for 12 weeks. Efficacy measures assessed manic symptoms, aggression, anxiety, depression, global clinical severity, and impairment. Safety measures included body mass index, serum prolactin, extrapyramidal adverse effects, and electrocardiogram. At the end of the study, all patients improved in all efficacy measures. Both treatments showed similar efficacy in reducing manic symptoms and aggression. Quetiapine was more effective in improving anxiety and depressive symptoms. A change in body mass index was found, and in a post hoc analysis, it was significant only in the risperidone group. Prolactin significantly increased only in the risperidone group. In BD type II, CD comorbidity, quetiapine, or risperidone monotherapy may be effective and relatively safe, although the small sample size, the limited duration of the study, and the design (lack of a blind assessments and of a placebo group) make it difficult to draw definitive conclusions.